Iot Based predication Analysis System for Precision Agriculture - Deshkar, Trupti; Ajani, Samir (International Journal of Computer Sciences and Engineering, 2025)
In India sustainable agriculture development is essential to meet food demands, economic growth and poverty reduction. Climate change having adverse effect on agriculture and traditional practices followed are planting, fertilizing and harvesting against the predetermined schedule. Precision agriculture can be used to mitigate the climate change. The work objective is optimal usage of water in irrigation, proper nutrient management to plant and avoid crop losses due to diseases and pests with proper scheduling of sprays. In this context, we have proposed an agro advisory system for the pomegranate field. Wireless sensor network is deployed on field and will continuously monitoring real time environmental, soil, hydrological and crop specific parameters. Those are important for growth, productivity and quality in agriculture. An agro advisory will be disseminated to the farmers according to real time field conditions . The experimental result analysis of proposed system shows improvement over traditional followed methods.